2022
DOI: 10.1002/cdq.12309
|View full text |Cite
|
Sign up to set email alerts
|

Emotional anticipation of the school‐to‐work transition: A multigroup latent profile analysis

Abstract: This study extends the investigation of future-oriented emotions by investigating students' emotional anticipation profiles at the prospect of the school-to-work transition. Among 2882 students, latent profile analysis revealed the emergence of four qualitative and quantitative distinct profiles. We also examined the profile similarity across gender, educational type, and the remaining time before the transition. Men and women exhibited both qualitative (i.e., profile shape and prevalence) and quantitative (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Our findings also complement the literature on future-oriented emotions, as little research has jointly examined both anticipatory and anticipated emotions simultaneously. Overall, our results echo and replicate previous findings regarding profiles of future-oriented emotions at the prospect of other important educational and career transitions such as the transition to university or the school-to-work transition (Parmentier et al, 2022a, 2022b). These findings bring important implications for the relationship between emotions and job search outcomes (Côté et al, 2006; Crossley & Stanton, 2005; da Motta Veiga & Turban, 2014; Kim & Lee, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings also complement the literature on future-oriented emotions, as little research has jointly examined both anticipatory and anticipated emotions simultaneously. Overall, our results echo and replicate previous findings regarding profiles of future-oriented emotions at the prospect of other important educational and career transitions such as the transition to university or the school-to-work transition (Parmentier et al, 2022a, 2022b). These findings bring important implications for the relationship between emotions and job search outcomes (Côté et al, 2006; Crossley & Stanton, 2005; da Motta Veiga & Turban, 2014; Kim & Lee, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…Anticipatory and anticipated emotions were measured using an adapted measure of Baumgartner et al (2008) that has already been successfully adapted in other contexts and career transitions (Parmentier et al, 2022a(Parmentier et al, , 2022b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As subgroups of the population may experience and anticipate the labour market and career development differently (Kanfer et al, 2001), we decided to examine whether the correlation effect sizes may be affected by whether participants were students or workers. Indeed, it has been demonstrated that the emotions that individuals anticipate and experience at the prospect of future transitions play an important role in how they visualize their transition and how to cope with it (Parmentier et al, 2021;Parmentier, Pirsoul, Bouchat, et al, 2022). According to the career stage perspective of Super (1957), we also think that workers have a higher level of experience in the labour market when compared to students and, in the end, are more confident in coping with their transition and career development.…”
Section: Sample Type (Workers Vs Students)mentioning
confidence: 99%
“…The preparation of leaving university life for a full-time job involves many challenges, such as developing clear career goals, making important career decisions, and anticipating and preparing for entry into the world of work (Akkermans et al, 2021). This period may lead to the experience of various emotions that could influence career choices and career behaviors (Parmentier et al, 2022). In this sense, emotional intelligence has received increasing attention as an important self-regulatory resource to respond adaptively to career events such as the school-to-work transition (Coetzee & Beukes, 2010).…”
mentioning
confidence: 99%